2021
DOI: 10.1007/s40200-021-00888-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic on glycemic control in patients with diabetes mellitus in Turkey: a multi-center study from Kocaeli

Abstract: Aims The aim of this study is to determine the impact of the COVID-19 pandemic on the management and disease control of the patients with diabetes mellitus in Kocaeli. Methods This study was carried out in six leading central hospitals in five major districts of Kocaeli. The study was conducted between June 2020 and November 2020. The patients who had previous admissions to these clinics within 6 months prior to the pandemic were enrolled in the study. Results A total of 283 patients were enrolled in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…years the HbA1c values increased slightly, despite treatment intensification. The results are in concordance with some but not all studies that evaluated the glycemic control during COVID-19 pandemic in patients with T2DM, as some of them showed deterioration of HbA1c values, others indicated an improvement, and others reported no change [19][20][21][22]. However, our results are in accordance with a systematic review that included data from 1823 patients with T2DM (and showed a mean increase in HbA1c of +0.14 [95%CI: −0.13 to 0.40]), and with the results of a meta-analysis of 11 studies (n=16,895) indicating a significant increase of HbA1c levels (0.34% [95%CI: 0.30 to 0.38]) during the COVID-19 pandemic [23,24].…”
Section: Discussionsupporting
confidence: 90%
“…years the HbA1c values increased slightly, despite treatment intensification. The results are in concordance with some but not all studies that evaluated the glycemic control during COVID-19 pandemic in patients with T2DM, as some of them showed deterioration of HbA1c values, others indicated an improvement, and others reported no change [19][20][21][22]. However, our results are in accordance with a systematic review that included data from 1823 patients with T2DM (and showed a mean increase in HbA1c of +0.14 [95%CI: −0.13 to 0.40]), and with the results of a meta-analysis of 11 studies (n=16,895) indicating a significant increase of HbA1c levels (0.34% [95%CI: 0.30 to 0.38]) during the COVID-19 pandemic [23,24].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, patients were not familiarized with healthy lifestyle habits [ 5 ]. Surprisingly, some studies showed that glycemic control has not changed and even improved during lockdown [ 6 , 7 , 8 , 9 ]. It was also confirmed that patients with diabetes had a higher risk of developing COVID-19 and diabetes-related late complications during the pandemic [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it appears that lockdown and the restrictions of outdoor activity reduced the risk of trauma and DFU occurrence which may have resulted in a lower number of newly diagnosed patients with DFU. As mentioned above, some studies showed, for example, that glycemic control improved during the lockdown, so it is important to verify whether the impact of the pandemic was negative or positive for patients with DFU [ 5 , 6 , 7 , 8 , 9 ]. We would like to present the first data from the national registry gathered from the Polish population comparing the number of hospitalizations, amputations, and death rate among patients with DFU in 2020 in a country with a relatively low healthcare expenditure in comparison with Western Europe and the United States.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the systematic review showed that the COVID-19 outbreak did not significantly change HbA1c (%) (n = 5) [30] , [33] , [34] , [35] , [36] . Deteriorated HbA1c (%) (n = 4) [37] , [38] , [39] , [40] were reported in Japan and Korea, which did not implement lockdown, and in Italy and Turkey, which imposed strict lockdown regulations.…”
Section: Resultsmentioning
confidence: 98%
“…6b ). For TG, deterioration [35] , [37] and stability [30] , [34] were equally reported, but its recalculated WMD suggests a significant increase (16.34, 95%CI 5.10 – 27.58) after removing D’Onofrio et al [30] based on the sensitivity analysis for reducing the potential publication bias.
Fig.
…”
Section: Resultsmentioning
confidence: 99%